Mapping Technological Innovation for the Implementation of Green Logistics in the Indonesian Courier Express Parcel (CEP) Industry - Veronica, Veronica; Irenita, Novembriani (Dinasti Publisher, 2025)
The rapid growth of the Indonesian Courier, Express, and Parcel (CEP) sector, fueled by e-commerce, has brought economic benefits but also significant environmental challenges. This research explores the potential of technology to implement green logistics practices within the Indonesian CEP industry, contributing to the global sustainability goals. A comprehensive literature review identified key technologies like electric vehicles, drones, AI, IoT, and sustainable packaging as crucial enablers of green logistics. Challenges such as high initial costs and regulatory hurdles were acknowledged. A proposed framework integrating these technologies into CEP operations was refined based on expert interviews, emphasizing the Indonesian context and the need for government support and incentives. The research concludes that a technology-driven approach to green logistics is vital for the CEP sector's sustainable future, highlighting potential benefits and addressing implementation challenges. The refined framework provides a practical roadmap for companies in Indonesia to adopt green technologies and contribute to a greener ecosystem. Future research directions include investigating the economic impact of green logistics on the Indonesian CEP sector and exploring the role of consumer awareness and behavior in driving sustainable practices.